Human Metapneumovirus in Severe Respiratory Syncytial Virus Bronchiolitis - Julie Greensill; Paul S. McNamara; Winifred Dove; Brian Flanagan; Rosalind L. Smyth; C. Anthony Hart (Emerging Infectious Diseases, 2003)
Reverse transcription-polymerase chain reaction was used to detect segments of the M (matrix), N (nucleoprotein), and F (fusion) genes of human metapneumovirus in bronchoalveolar fluid from 30 infants with severe respiratory syncytial virus bronchiolitis. Seventy percent of them were coinfected with metapneumovirus. Such coinfection might be a factor influencing the severity of bronchiolitis.